Prevalence of severity and type of hearing loss in Rheumatoid Arthritis patients: Hearing loss in Rheumatoid Arthritis Patients - Jabbar, Muzamal; Badar, Asfara; Mehboob, Maria; Shanawar, Minahil; Tahir, Fatima; Azzam Khan, Muhammad; Anwar Faridi, Tallat (Pakistan Journal of Health Sciences, 2022)
Rheumatoid arthritis (RA) is a chronic heterogeneous autoimmune disease characterized by painful joint inflammation which may cause destructive bone erosions. It also affects the auditory system and cause hearing loss. Objective: To find out the prevalence of Severity and type of Hearing Loss in Rheumatoid Arthritis Patients. Methods: Cross sectional descriptive study was conducted to find the prevalence of Severity and type of Hearing Loss in Rheumatoid Arthritis Patients. The study was performed at DHQ Hospital Bhimber, Mayo Hospital Lahore. The duration of data collection was 6 months (April 2022 to September 2022). Non-probability convenient sampling technique was used for data collection. Patients of both gender with ages 30 to 50 years were included. Patients with rheumatoid arthritis with other co-morbid factors were excluded. Results: Out of 117 patients, there were 33 (28.2%) male patients and 84 (71.8%) female patients. Most patients were in age group 41-45 years 38 (32.5 %). There were 19 (16.2%) lower class patients, 93 (79.5%) middle class patients and 5 (4.3%) upper class patients. The prevalence of Hearing Loss in Rheumatoid Arthritis patients was high 70 (59.5%). Sensorineural hearing loss 66 (56.4) was most prevalent. Majority of them had mild to moderate degree hearing loss 50 (42.7%). Conclusion: The study showed the prevalence of Hearing Impairment in Rheumatoid Arthritis was high. The result of this study also concluded that majority of the patients had mild to moderate degree sensorineural hearing loss.